Starr Carter’s intersectional resistance in Angie Thomas’ The Hate U Give - Jorgina Fátima Antunes dos Santos Cameirão Ataide; Mateus Rudi Supsiadji (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2026)
This study analyzes Starr Carter’s voice as a form of resistance shaped by her intersectional identity in Angie Thomas’s The Hate U Give (2017). The research focuses on the relationship between intersectional discrimination and the development of resistance as represented through Starr’s experiences as a young Black girl. Drawing upon Kimberlé Crenshaw’s intersectionality theory and resistance theory, this study investigates two major issues: the types of intersectional discrimination that shape Starr Carter’s voice and the ways in which her voice functions as resistance to racism and systemic injustice. This research employs a descriptive qualitative method with an interpretative approach. The primary data are obtained from the novel The Hate U Give, particularly dialogues, narration, and character descriptions related to Starr’s identity, experiences, and responses to oppression. Secondary sources, including books and scholarly journals on intersectionality, resistance, and literary criticism, are also utilized to support the analysis. The findings reveal that Starr’s voice is shaped by three interconnected forms of discrimination: racial discrimination, gendered expectations, and age-based discrimination or adultism. Racial discrimination is represented through police violence, racial profiling, media stereotyping, and the criminalization of Black identity. Gendered expectations pressure Starr to regulate her emotions and language to avoid stereotypes associated with Black girls, while adultism causes her testimony and experiences to be underestimated despite her role as the primary witness to Khalil’s death. These intersecting oppressions initially produce fear, trauma, and silence. However, Starr gradually develops critical awareness and transforms her silence into resistance. Her voice evolves through three stages: silent resistance, personal resistance through testimony and truth-telling, and collective resistance through public protest. Ultimately, this study demonstrates that The Hate U Give portrays voice as a powerful instrument of empowerment, identity affirmation, and resistance against systemic injustice within contemporary young adult literature.